Pyrolysis of Spirulina platensis Residue: Effect of Temperature without and with Fe-oxide catalyst - Siti Jamilatun; Tyas Aji Kurniawan; Adhi Chandra Purnama; Irfan Maulana Putra (Universitas Ahmad Dahlan, 2020)
The limited reserves of fuel must resolve immediately. One of the renewable energy solutions that have the potential to come from biomass sources is microalgae. The advantages of microalgae compared to other biomass is the oil produced, the speed of growth, and it does not interfere with food availability. The processing of residual Spirulina platensis microalgae (SPR) by pyrolysis is exciting to do, does not cause pollution, and the technology is simple. This study's purpose was SPR pyrolysis with a grain size of 140 mesh without and with five (5) wt.% Fe-oxide catalyst. The variables studied were temperature on the yield of bio-oil products, water phase, charcoal, and gas. Pyrolysis was carried out in a fixed bed reactor at 300, 400, 500, 550, and 600 â°C. The higher the pyrolysis temperature, the higher the bio-oil yield, with the optimum catalyst at 400 â°C produced 15.34% and without a catalyst at a temperature of 500 â°C, namely 15.00%. The water yield phase in the range of 300-600 â°C is higher for catalyst use (30-39 %) than without catalyst (13.75-22.25%). The higher the pyrolysis temperature, the lower the yield char. The yield of gas without a catalyst was higher in the range of 30.69-38.94% compared to catalyst 12.58-26.18%. At a temperature of 300 â°C without a catalyst, the conversion obtained was 48.69%, while with a catalyst, 60.08%